2007
DOI: 10.1590/s1413-81232007000600031
|View full text |Cite
|
Sign up to set email alerts
|

As práticas profissionais no campo público de atenção à saúde bucal: o caso de dois municípios da Bahia

Abstract: This paper examines the working facilities and processes of dentists in the primary healthcare systems of two towns in Bahia State, Brazil, striving to analyze the extent to which factors related to dental care, training, placement and professional profiles influence their practices. Semi-structured interviews were conducted with nine dentists in both towns, with work process organization patterns in Municipality C being closer to the structuring principles of Brazil's National Health System than in Municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
0
15
0
6
Order By: Relevance
“…The way of organization of referral of users to specialties is also one of the challenges that need to be addressed 24,25 , because the existence of bureaucratic flows and limitations for the care provided to users submitted by BHU shows obstacles to the coordination and integrality of care, as found of the present study and research developed in Natal (RN) 26 . Knowing the itinerary of users and the reasons for 'choices' and 'possibilities' can be a way to reorient services and expand access.…”
Section: Discussionmentioning
confidence: 78%
“…The way of organization of referral of users to specialties is also one of the challenges that need to be addressed 24,25 , because the existence of bureaucratic flows and limitations for the care provided to users submitted by BHU shows obstacles to the coordination and integrality of care, as found of the present study and research developed in Natal (RN) 26 . Knowing the itinerary of users and the reasons for 'choices' and 'possibilities' can be a way to reorient services and expand access.…”
Section: Discussionmentioning
confidence: 78%
“…One study showed that the ethos of private dental practice is present in various ways, appearing in both the professionals' practice and expectations 28 . Although the primary health care institutional project did accomplish some changes in the agents' activity as much as supported by committed local healthcare management, the ethos of private practice still prevails.…”
Section: Discussionmentioning
confidence: 99%
“…The hegemony of the private sector appears to have an influence of the professional practice of the dentists in public service 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The monthly income of dentists in public service has not been much evaluated in the literature 18,[22][23] .…”
Section: Discussionmentioning
confidence: 99%